Proceedings of the 7th Workshop in Primary and Secondary Computing Education 2012
DOI: 10.1145/2481449.2481466
|View full text |Cite
|
Sign up to set email alerts
|

Promoting computational thinking with programming

Abstract: The term computational thinking has received some discussion in the field of computer science education research. The term is defined as the concept of thinking about problems in a way that can be implemented in a computing device. Of course, after having thought about a problem using computational thinking skills, the next step should be to use programming skills to implement the solution. This work in progress is exploring ways in which programming can be employed as a tool to teach computational thinking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 18 publications
2
68
0
13
Order By: Relevance
“…Many have recently suggested ways of implementing computational thinking into the curriculum (Barr and Stephenson 2011, Webb and Rosson 2013, Brennan and Resnick 2012, Lee et al 2011, Selby 2012, Yadav et al 2011, Van Dyne and Braun 2014, Sengupta et al 2013). In our research we find teachers describe using a variety of activities that develop computational thinking skills in learners.…”
Section: Embedding Computational Thinkingmentioning
confidence: 99%
“…Many have recently suggested ways of implementing computational thinking into the curriculum (Barr and Stephenson 2011, Webb and Rosson 2013, Brennan and Resnick 2012, Lee et al 2011, Selby 2012, Yadav et al 2011, Van Dyne and Braun 2014, Sengupta et al 2013). In our research we find teachers describe using a variety of activities that develop computational thinking skills in learners.…”
Section: Embedding Computational Thinkingmentioning
confidence: 99%
“…If initiated at the primary stage of education, we also call it primary programming. An interesting study on connection of computational thinking and programming can be found in (Selby, 2012). There are many age-appropriate tools and environments that allow us to design meaningful and engaging elementary programming activities while respecting children's developmental stage.…”
Section: Programming As a Component Of School Informaticsmentioning
confidence: 99%
“…Computational thinking draws on computational practices that have been strengthened in recent years by developments in the field of computer science [2,17]. Key aspects of computational thinking are: 1) view of problems with inputs and computations following a precise algorithm that leads to clear outputs; 2) reformulating a seemingly difficult problem into one or more problems we know how to solve, perhaps by reduction, embedding, transformation, or simulation; 3) thinking recursively; 4) approaching problems using parallel processing; and 5) using abstraction and decomposition when attacking a large complex task or designing a large complex system [15].…”
Section: Computational Thinkingmentioning
confidence: 99%